Shuttling as a Strategy to Control the Regiochemistry of Bis‐Additions on Fullerene Derivatives. Issue 12 (28th January 2016) - Carini, Marco; Da Ros, Tatiana; Prato, Maurizio; Mateo‐Alonso, Aurelio
Abstract: The reactivity of a fullerene‐stoppered rotaxane, a C60 monoadduct, towards a second cycloaddition reaction is explored. The close proximity of the macrocycle to the fullerene sphere is able to allosterically influence the second cycloaddition reaction, giving rise to a selected mixture of bis‐adducts. Abstract : The reactivity of a fullerene‐stoppered rotaxane, a C60 monoadduct, towards a second cycloaddition reaction is explored. The close proximity of the macrocycle to the fullerene sphere allosterically influences the second cycloaddition reaction, giving rise to a selected mixture of bis‐adducts.